РЕАБИЛИТАЦИЯ ДЕТЕЙ С ЮВЕНИЛЬНЫМ РЕВМАТОИДНЫМ АРТРИТОМ - Мадаминова, Малика Шавкатовна; Толипова, Ноила Кудратовна; Юсупова, Гулноза Амониллаевна; Мусаева, Амина Файзуллаевна (Медицина: теория и практика, 2020)